ANALYSIS OF MUSLIM STUDENTS’ INTENTION IN INFAQ AND SHADAQAH THROUGH ONLINE PLATFOMS - Maulana, Haviv Isya; Sudarsono, Heri (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2024)
This study aims to analyze what factors influence the intention of Muslim students to give infaq and shadaqah through online platforms using the Unifield Theory of Acceptance and Use of Technology (UTAUT) approach. This type of research used is quantitative research. The population and sample used in this study were Muslim students who had made or given information and articles online as many as 298 respondents. The results in this study indicate that the performance of expectancy, social influence, and trust has a positive and significant effect on the behavioral intention of Muslim students to spend and give shadaqah online. effort expectancy, facilitating conditions have a positive but not significant effect on the behavioral intention of Muslim students to spend and study online. Facilitating conditions has a significant effect on the user behavior of Muslim students to spend and study online. Behavioral intention has a significant effect on the user behavior of Muslim students to spend and study online.